The Domestication of Catherine Earnshaw: Tensions of Identity in Emily Brontë‘s Wuthering Heights - Cabello Bravo, Andy (Journal of Artistic Creation and Literary Research, 2025)
The tenor of Catherine Earnshaw throughout Wuthering Heights has been construed and revised in many different ways. Gender, psychoanalytic, post-structuralist readings have offered interpretations as to her pilgrimage, her vindications, or her identity; but the core of what Catherine ultimately is and is contained by traces back to her childhood, Heathcliff, and the moors, where she abides by a state of spiritual wholeness. It is in this narrative gap, where no record from Nelly Dean exists, that her identity is formed. The fact that this period is not subjected to language entails that the primary meaning is left intentionally untouched; its content is too strange to be told—it needs to remain unknown. Through her coming of age this wholeness inherent to her past will be lost. Her evolution in the novel, lastly, will represent the struggle born in coexistence of Victorian domestic values with the unconscious desire to be herself again. This essay intends to shed light on the elements that permit us understand Catherine‘s journey as one of domestication of strangeness, and the tensions of identity that grow in her self with it.